Synthesis of calcium carbonate in the presence of polymers under ultrasonic waves - Kirboga, Semra; Oner, Mualla (BIOINTERFACE RESEARCH APPLIED CHEMISTRY, 2016)
Calcium carbonate (CaCO3) was synthesized in the presence of the water-soluble polymers Poly(Vinyl Sulfonic Acid) (PVS) and Carboxymethyl Inulin (CMI) using sonication in aqueous solution medium. We have investigated the effect of the polymers and the amplitude of sonicator on calcium carbonate crystallization. Calcium carbonate crystals synthesized with and without ultrasound were characterized by X-ray diffraction (XRD), Fourier transform infrared spectrometer (FT-IR), scanning electron microscopy (SEM) and particle sizer. A mixture of vaterite and calcite was obtained in the presence of CMI, whereas there was only calcite polymorph in the absence of polymers. Vaterite was obtained with the introduction of PVS. The addition of polymers caused to the change in morphology and polymorph of calcium carbonate. The particle size of calcium carbonate crystals decreased with increasing of sonicator amplitude and polymers concentration. The results showed that the sonicator amplitude and polymers affected the calcium carbonate crystallization.
Keywords: Calcium carbonate; precipitation; polymorph; vaterite; calcite; CARBOXYMETHYL INULIN; OXALATE CRYSTALLIZATION; ASSISTED SYNTHESIS; AQUEOUS-SOLUTION; GROWTH; NANOPARTICLES; CACO3; POLYELECTROLYTES; Chemistry